Online Learning Assistance At Perum Tamara - Purnomo, Andhika Julio; Oktaviani, Tesa; Aditama, Raihan Geraldy; Islami Dini, Nurul Aeni; Daniati, Nia; Illena Karel, Maria; Nurjanah, Dewi; Rizki, Chandra Muhammad; Riyadi, Anita Nurlaeli; Amna, Aldi Mustafid; Suciani, Ai Yuni; Pratiwi, Mega Silvia; wagiman, Acep (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The Covid-19 virus has spread in Indonesia, various efforts have been made to suppress the spread of this virus, one of which is the implementation of online learning. For this reason, the implementation of online learning is considered able to reduce the spread of the existing virus. This online learning has several obstacles. One of them is that many students do not have independence in learning. So the role of parents in accompanying their children in learning is very important. However, the problem is that many parents cannot accompany their children to study as happened at Perum TAMARA. This is because parents do not have the ability to educate and or parents are busy working, the relationship between parents and students is uncertain and children are slow to learn. Even though the role of parents is very influential on the success of online learning. For this reason, the purpose of this study is to find out how the role of parents is to be ready to do online learning for their children. Alternative KKNT UMTAS Group 13 has a program for online learning assistance. Where children who are around Perum and around Perum will be accompanied when online learning or doing school assignments that are not yet understood.